Evaluation Serum IL-22, TNF-α as a Potential Diagnostic Biomarker in Iraqi Psoriasis Patients - Alkilabi, Amer Alwan; Dheeb, Israa Abdul Wahid (Medical Science Journal for Advance Research, 2025)
Background: Psoriasis (PS) is a chronic, multifactorial autoimmune skin disease with systemic involvement. Psoriasis affects approximately 2-3% of the global population. The disease is prone to recurrence, characterized by intervals of increased severity and remission. Despite the lack of a specific cause, psoriasis is considered to be complex, it involves a combination of genetic, immunological, and environmental components. Goal of study: Our study aimed to evaluate the serum levels of IL-22, TNF-α in Iraqi PS patients and to assess its potential diagnostic significance. Material and Methods: A case-control study involved 40 clinically diagnosed PS patients and 40 healthy controls matched for age and sex. Serum samples were collected, separated by centrifugation, and stored at –40°C. IL-22, TNF-α levels were measured using a sandwich ELISA kit. Results: Clinical data were recorded for correlation analysis, including disease duration, disease severity, and psoriasis. Serum IL-22 and TNF-α levels were significantly elevated in PS patients compared to healthy controls (p< 0.001). Higher IL-22 and TNF-α concentrations were associated between serum IL-22 and severity, duration, or PASI score. ROC curve analysis indicated good diagnostic potential, with TNF-α as a promising non-invasive biomarker. Furthermore, elevated IL-22 and TNF-α levels were linked to the important inflammatory factors in the pathophysiology of psoriasis. Conclusion: Serum IL-22 and TNF-α levels may serve as valuable diagnostic biomarkers in Iraqi PS patients. Further large-scale studies are needed to validate its clinical utility in PS management.